Prevalence and risk factors for chalazion in an older veteran population. Issue 9 (31st March 2021) - Patel, Sneh; Tohme, Natalia; Gorrin, Emmanuel; Kumar, Naresh; Goldhagen, Brian; Galor, Anat
Abstract : Background: Chalazia are common inflammatory eyelid lesions, but their epidemiology remains understudied. This retrospective case–control study examined the prevalence, risk factors and geographic distribution of chalazia in a large veteran population. Methods: Data on all individuals seen at a Veterans Affairs (VA) clinic between October 2010 and October 2015 were extracted from the VA health database. Subjects were grouped based on International Classification of Diseases, Ninth Revision (ICD-9) code for chalazion. Univariable logistic regression modelling was used to identify clinical and demographic factors associated with chalazion presence, followed by multivariable modelling to examine which factors predicted risk concomitantly. All cases were mapped across the continental US using geographic information systems modelling to examine how prevalence rates varied geographically. Results: Overall, 208 720 of 3 453 944 (6.04%) subjects were diagnosed with chalazion during the study period. Prevalence was highest in coastal regions. The mean age of the population was 69.32±13.9 years and most patients were male (93.47%), white (77.13%) and non-Hispanic (93.72%). Factors associated with chalazion risk included smoking (OR=1.12, p<0.0005), conditions of the tear film (blepharitis (OR=4.84, p<0.0005), conjunctivitis (OR=2.78, p<0.0005), dry eye (OR=3.0, p<0.0005)), conditions affecting periocular skin (eyelid dermatitis (OR=2.95, p<0.0005), rosacea (OR=2.50, p<0.0005)), allergic conditions (history of allergies (OR=1.56, p<0.0005)) and systemic disorders (gastritis (OR=1.54, p<0.0005), irritable bowel syndrome (OR=1.45, p<0.0005), depression (OR=1.35, p<0.0005), anxiety (OR=1.31, p<0.0005)). These factors remained associated with chalazion risk when examined concomitantly. Conclusion: Periocular skin, eyelid margin and tear film abnormalities were most strongly associated with risk for chalazion. The impact of environmental conditions on risk for chalazion represents an area in need of further study.